Helminths of Wild Predatory Mammals of Ukraine. Nematodes - Varodi, E. I.; Malega, A. M.; Kuzmin, Y. I.; Kornyushin, V. V. (Vestnik Zoologii, 2017)
Abstract The article summarizes information on the nematodes parasitic in wild Carnivora of Ukraine. Totally, 50 species of nematodes are known to parasitise carnivorans in the country, 30 species were registered in the present study. Nematodes were found in 14 species of examined hosts from the families Canidae, Mustelidae and Felidae. Maximum diversity of nematodes of carnivorans was observed in Polissia (forest zone in the north of the country) and in Kherson Region in the south. Hosts from the family Canidae harboured 19 nematode species; studied species of the Mustelidae were infected with 15 nematode species, 6 of them were also found in Canidae. The wildcat (Felis silvestris Schreber) and the lynx (Lynx lynx Linnaeus) harboured only two species of nematodes, both are specific parasites of these hosts. The most comprehensive information concerns the nematode communities of the red fox (Vulpes vulpes Linnaeus) and the wolf (Canis lupus Linnaeus), with 19 and 9 nematode species found, correspondingly. From 1 to 6 nematode species were found in other species of carnivorans.